The Effect of Wave Squat and Double Leg Hop Progression With a Leg Press And Calf Sitting On Leg Muscle Strength And Power - Usbah, Muh (Universitas Negeri Semarang, 2017)
The purposes of this research were to analyze (1) the effect of wave squat to increase leg muscle strength; (2) the effect of double leg hop progression towards an increase in leg muscle strength; (3) the effect of leg press exercise to increase leg muscle strength; (4) the effects of exercise sitting calf to the power of leg muscles; (5) different effects of leg press and sitting calf to increase leg strength; (6) different effects of wave squat and double-leg hop progression to the increase of the leg power. The type of research was quantitative with quasi-experimental methods. The research design was matching only design and data analysis was using Anova. The data retrieval process performed by leg power jump test DF and leg muscle power, back and leg dynamometer were used during the pretest and posttest. Furthermore, the outcome data was analyzed using SPSS 16.0 series. The results showed that there was a significant difference between the wave squat compared to double leg hop workout progression in leg muscle strength; with the Sig. 0,000 less than 0.05 (p 0.05). whereas for leg power there was a significant difference between the leg press exercise when compared with calf sitting exercises to improve leg power proved; with the Sig. 0,000 less than 0.05 (p 0.05) From the t-test result, there was an increase in leg muscle strength and power in each group after being given training.